Coopetition Strategy for Micro Entrepreneurs : A Case Study of Rural Artisan Cluster - Prajapati, Keerti (AMC Indian Journal of Entrepreneurship, 2019)
Rural enterprises are generally community based traditional businesses located in a cluster. Research in the field has pointed out that coopetition network, co-existence of cooperation, and competition prove to be the key determinants which enhance enterprise performance. However, research on micro entrepreneurs in rural artisan cluster is negligible and few that are conducted, are limited to economic perspective. This research attempts to explain intricate dynamics of coopetition among rural artisan entrepreneurs and between the entrepreneurs, buyers, and suppliers within the textile cluster in Kutch, Gujarat by using social network perspective. Case study approach was chosen to understand the dynamics of cooperation and competition of cluster micro entrepreneurs in a small artisans’ cluster in the district of Kutch (India). The case study is based on in-depth interviews and observations of weaver entrepreneurs. The findings of the case study suggest that the relationships in an artisan cluster are far more complex than the way competition and cooperation are understood. The study is a contribution to the literature on micro entrepreneurship and has major implications for policy on cluster development. The research fills gaps of lack of studies of micro enterprise clusters in India. The study helps to understand how micro entrepreneurs use coopetition as a strategy to increase their enterprise performance.